Trichoribates (Trichoribates) myricus Gjelstrup and Solhoy 1994 - Murvanidze, Maka; Cilbircioğlu, Cihan; Özdemir, Esengül; Inak, Emre (Zenodo, 2020)
Trichoribates (Trichoribates) myricus Gjelstrup and Solhöy, 1994 * Material – New record for Turkey. Two specimens in Aluç Dağı Natural Park, Ankara, N 40° 49′ 75.37′′, E 32° 58′ 26.46′′, alt. = 1402 m, 15 June 2018, soil. Global distribution – Euroatlantic. Ecology – Humid meadows, forest soils. Remarks – Measurements: Body size of Turkish individuals (570 × 345 µm) is smaller than provided in original description (650 × 420 µm) (Gjelstrup and Solhöy 1994), however Weigmann (2006) reports smaller size (555–670 µm), so that our findings match within the given range. Weigmann (2006) also indicates size of nogastral setae up to 60 µm, while for Turkish individuals these setae are even shorter, 45 µm. This is the first record of the species out of Europe. Previous findings were known from Iceland (Gjelstrup and Solhöy 1994) and Germany (Weigmann 2006). The species was described from bogs and swamps in Island and was additionally found in Schleswig-Holstein and Odertal in Germany (Weigmann 2006). Finding site in forested area of Turkey adds more information about habitat preferences for this species.

Published as part of Murvanidze, Maka, Cilbircioğlu, Cihan, Özdemir, Esengül & Inak, Emre, 2020, Checklist of oribatid mites (Acari: Oribatida) of the Central Black Sea basin of Turkey with new records for the country, pp. 255-277 in Persian Journal of Acarology 9 (3) on page 268, DOI: 10.22073/pja.v9i3.61909, http://zenodo.org/record/5236444
Keywords: Trichoribates myricus; Arthropoda; Trichoribates; Arachnida; Ceratozetidae; Animalia; Biodiversity; Sarcoptiformes; Taxonomy; 15. Life on land